Electromagnetic shielding nanofiber composite membrane and preparation method thereof

By using PVA-co-PE substrates and carboxylated carbon nanotubes, copper nanowires and nickel ferrite fillers in electromagnetic shielding materials, the three-dimensional mesh porous structure is solved, and the problem of poor mechanical properties of existing electromagnetic shielding materials is solved. , realizes efficient electromagnetic shielding and good mechanical properties.

CN119507258AActive Publication Date: 2025-02-25WUHAN TEXTILE UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411432206.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials are obtained through stacking and assembly, and their mechanical properties are deviated and they are prone to slip or cracking. How to simultaneously improve the electromagnetic interference shielding and mechanical properties of the material is a technical problem that needs to be solved urgently.

Method used

PVA-co-PE is used as the substrate, carboxylated carbon nanotubes, copper nanowires and nickel ferrite are used as fillers, and the fillers are uniformly loaded into the substrate through vacuum-assisted filtration, cross-linking and hot pressing processes to form a three-dimensional network shaped porous structure.

Benefits of technology

The prepared nanofiber composite film has excellent electromagnetic shielding performance and mechanical properties, with an electromagnetic shielding performance of 59dB and a maximum tensile stress of 12MPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507258A_ABST
    Figure CN119507258A_ABST
Patent Text Reader

Abstract

The invention provides an electromagnetic shielding nanofiber composite membrane and a preparation method thereof, and belongs to the technical field of electromagnetic shielding material preparation. The electromagnetic shielding nanofiber composite membrane provided by the invention comprises a three-dimensional skeleton base material, and a conducting medium and a magnetic medium which are uniformly dispersed in the three-dimensional skeleton base material, and a special three-dimensional net-shaped porous structure is formed between the base material and the conducting medium and between the base material and the magnetic medium through lap joint and adsorption. The thickness of the composite film provided by the invention is 20-30 [mu] m, the electromagnetic shielding effectiveness reaches 59dB, and the maximum tensile stress reaches 12MPa. The preparation method of the composite film comprises the following steps: uniformly loading the carboxylated carbon nanotubes, the copper nanowires and the nickel ferrites into PVA-co-PE nanofibers through vacuum-assisted filtration, crosslinking and hot pressing procedures, and carrying out one-time suction filtration to form the composite film, so that the preparation method is simple, and the composite film has relatively good repeatability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electromagnetic shielding material preparation, and specifically to an electromagnetic shielding nanofiber composite membrane and a preparation method thereof. Background Art

[0002] The rapid development of electronic information technology has brought many conveniences to society, but the excessive electromagnetic radiation generated will not only affect human health, but also affect the normal operation of equipment or electronic systems. Therefore, whether it is nuclear power plants, transformers, aerospace systems, aircraft, ships, 5G communications or medical equipment, electromagnetic shielding materials are needed to block the propagation of electromagnetic waves and reduce the interference of electromagnetic radiation. From the transmission line theory of electromagnetic shielding mechanism, it can be seen that the attenuation of electromagnetic by electromagnetic shielding body is mainly based on its reflection and absorption of electromagnetic waves. The attenuation of electromagnetic waves is often achieved through electrical loss, magnetic loss and dielectric loss in reflection and absorption. In addition to having good electromagnetic shielding performance, good electromagnetic interference shielding materials must also have the characteristics of light weight, good flexibility, good chemical stability and good mechanical properties to be suitable for different scenarios and fields.

[0003] Metallic electromagnetic shielding materials have excellent electrical conductivity, electromagnetic interference shielding performance and thermal management performance, and are widely used in industry. However, due to the high density, low flexibility, poor mechanical properties and poor chemical corrosion resistance of such materials, their application is limited in many cases. Conductive polymer composites (CPCs) are composed of polymer matrix and conductive filler. They are easy to form, corrosion-resistant and have good mechanical properties. They are widely used in lightweight electromagnetic interference shielding and thermal management. At present, introducing magnetic media into CPCs and improving the interference shielding performance of electromagnetic shielding materials through the synergistic effect of magneto-electricity has become a new key research direction.

[0004] In the prior art, electromagnetic shielding materials are mostly designed as multilayer structures, such as gradient distribution multilayer structure design. By stacking composite material layers containing different fillers, electromagnetic shielding in a wider frequency range can be achieved; by stacking composite material layers with the same filler but gradually increasing filler proportions, interface differences can be reduced, reflectivity can be limited, and electromagnetic shielding performance can be improved. However, since such electromagnetic shielding materials are obtained by stacking and assembly, the mechanical properties are still biased and are prone to slippage or cracking during use. How to simultaneously improve the electromagnetic interference shielding performance and mechanical properties of the material is a technical problem that urgently needs to be solved.

[0005] In view of this, it is necessary to design an improved electromagnetic shielding nanofiber composite membrane and a preparation method thereof to solve the above problems. Summary of the invention

[0006] In view of the technical problems existing in the background technology, the present application provides an electromagnetic shielding nanofiber composite membrane and a preparation method thereof. The present application adopts PVA-co-PE as a substrate, carboxylated carbon nanotubes, copper nanowires and nickel ferrite as fillers, and the fillers are evenly loaded into the substrate through vacuum-assisted filtration, cross-linking and hot pressing processes. The substrate and the three fillers are overlapped and adsorbed to form a three-dimensional mesh porous structure. The prepared nanofiber composite membrane has excellent electromagnetic shielding performance and mechanical properties. The electromagnetic shielding effectiveness of the composite membrane reaches 59dB, and the maximum tensile stress reaches 12MPa.

[0007] In the first aspect, the embodiment of the present application provides an electromagnetic shielding nanofiber composite membrane, comprising a three-dimensional skeleton substrate, and a conductive medium and a magnetic medium uniformly dispersed in the three-dimensional skeleton substrate; the electromagnetic shielding nanofiber composite membrane has a three-dimensional mesh porous structure; the electromagnetic shielding nanofiber composite membrane has a thickness of 20-30 μm, an electromagnetic shielding effectiveness of 59 dB, and a maximum tensile stress of 12 MPa. Among them, the mass proportion of the three-dimensional skeleton substrate in the electromagnetic shielding nanofiber composite membrane is 94-99%.

[0008] In some embodiments, the conductive medium comprises carboxylated carbon nanotubes and copper nanowires, and the magnetic medium comprises nickel ferrite.

[0009] In some embodiments, the mass ratio of the carboxylated carbon nanotubes, the copper nanowires, and the nickel ferrite is (1-2.5):(1-1.5):1.

[0010] In some embodiments, the electromagnetic shielding nanofiber composite membrane uses PVA-co-PE nanofibers as a three-dimensional skeleton substrate, and the carboxylated carbon nanotubes, the copper nanowires and the nickel ferrite are uniformly loaded into the PVA-co-PE nanofibers through vacuum assisted filtration, crosslinking and hot pressing processes.

[0011] In some embodiments, the PVA-co-PE nanofibers, the carboxylated carbon nanotubes, and the copper nanowires are overlapped with each other to form a three-dimensional network porous structure.

[0012] In a second aspect, the present application provides a method for preparing the aforementioned electromagnetic shielding nanofiber composite membrane, comprising the following steps:

[0013] S1, isopropyl alcohol, deionized water and PVA-co-PE nanofibers are uniformly mixed using a high-speed shearing machine to prepare a PVA-co-PE nanofiber suspension with a fiber content of 1 wt%;

[0014] S2, mixing the PVA-co-PE nanofiber suspension prepared in step S1 with carboxylated carbon nanotubes, copper nanowires and nickel ferrite, stirring for 0.5-1h, and vacuum-assisted filtration to obtain a nanofiber composite membrane; the PVA-co-PE nanofibers account for 94-99% of the mass of the nanofiber composite membrane; the mass ratio of the carboxylated carbon nanotubes to the copper nanowires and the nickel ferrite is (1-2.5):(1-1.5):1;

[0015] S3, immersing the nanofiber composite membrane in a glutaraldehyde crosslinking agent with a concentration of 1.5 wt%, crosslinking is performed by ultraviolet radiation crosslinking method, and then naturally air-drying and hot pressing to obtain the electromagnetic shielding nanofiber composite membrane.

[0016] In some embodiments, in step S2, the preparation method of the carboxylated carbon nanotubes is to mix the multi-walled carbon nanotubes with concentrated nitric acid and ultrasonicate for 1-2 hours, add concentrated sulfuric acid, place at 55-65°C overnight, then add 2 times the volume of deionized water to dilute, freeze-dry, and obtain carboxylated carbon nanotube powder.

[0017] In some embodiments, in the method for preparing carboxylated carbon nanotubes, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 1:3.

[0018] In some embodiments, in step S3, the hot pressing method is to sandwich the air-dried nanofiber composite membrane between two polyimide films and place them together in a hot press at 100-105° C. for 60-65 seconds.

[0019] In some embodiments, in step S3, the time of UV radiation cross-linking is 3-3.5 hours.

[0020] The beneficial effects of this application are:

[0021] This application uses PVA-co-PE as the substrate, carboxylated carbon nanotubes (HOOC-MWCNT), copper nanowires (CuNWs) and nickel ferrite (NiFe 2 O 4 ), the fillers are evenly loaded into the substrate through vacuum-assisted filtration, cross-linking and hot pressing processes. The substrate and the three fillers overlap and adsorb to form a three-dimensional network porous structure. The prepared nanofiber composite membrane has excellent electromagnetic shielding performance and mechanical properties. The electromagnetic shielding efficiency of the composite membrane reaches 59dB, and the maximum tensile stress reaches 12MPa.

[0022] (1) The present application modifies carbon nanotubes by introducing carboxyl functional groups, so that the modified carbon nanotubes can produce hydrogen bonding effects with functional groups such as hydroxyl groups on PVA-co-PE nanofibers through cross-linking reactions, thereby generating hydrogen bonds and increasing the mechanical properties of the composite film.

[0023] (2) This application combines HOOC-MWCNTs, CuNWs and NiFe 2 O 4 The three fillers are composited to form a special three-dimensional porous structure through the overlap and adsorption between the substrate and the three fillers. Among them, the tubular and linear structures of carbon nanomaterials and copper nanomaterials effectively avoid agglomeration during the membrane preparation process. NiFe with an inverse spinel structure 2 O 4 Adsorbed on HOOC-MWCNTs and CuNWs, the heterogeneous contact surface between the three fillers is greatly increased, thereby increasing the dipole polarization effect, optimizing the impedance matching, and making the composite film have excellent electromagnetic shielding performance. When electromagnetic waves are incident on the composite film, the dielectric loss effect of HOOC-MWCNT, the dielectric shielding effect of CuNWs, and the NiFe 2 O 4 The magnetic loss effects cooperate with each other to form a "magnetic-electric" synergistic effect, which makes the electromagnetic waves repeatedly scattered and absorbed on the uneven surface of the composite film, achieving a good shielding effect.

[0024] (3) The electromagnetic shielding nanofiber composite membrane provided in the present application is a single-layer uniformly filled structure, which makes it easier to control product quality in actual production, and can be formed by one-time filtration, and the preparation method is simpler.

[0025] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 The figure is a flow chart for preparing the electromagnetic shielding nanofiber composite membrane;

[0028] Figure 2 The surface microstructure of PVA-co-PE nanofibers at 1000 times magnification;

[0029] Figure 3 The surface microstructure of the electromagnetic shielding nanofiber composite membrane prepared in Example 1 when magnified 10,000 times;

[0030] Figure 4The surface microstructure of the electromagnetic shielding nanofiber composite membrane prepared in Example 1 when magnified 1000 times;

[0031] Figure 5 The electromagnetic shielding effectiveness diagram of the composite membrane and PVA-co-PE nanofiber membrane prepared in Example 1 and Comparative Examples 5-6;

[0032] Figure 6 The mechanical properties diagram of the composite membrane prepared in Example 1 and Comparative Examples 7-8 and the PVA-co-PE nanofiber membrane. DETAILED DESCRIPTION

[0033] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0035] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0037] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0038] In the prior art, electromagnetic shielding materials are mostly designed as multilayer structures, such as gradient distribution multilayer structure design. By stacking composite material layers containing different fillers, electromagnetic shielding in a wider frequency range can be achieved; by stacking composite material layers with the same filler but gradually increasing filler proportions, interface differences can be reduced, reflectivity can be limited, and electromagnetic shielding performance can be improved. However, since such electromagnetic shielding materials are obtained by stacking and assembly, the mechanical properties are still biased and are prone to slippage or cracking during use. How to simultaneously improve the electromagnetic interference shielding performance and mechanical properties of the material is a technical problem that urgently needs to be solved.

[0039] In order to solve the above technical problems, the present application provides an electromagnetic shielding nanofiber composite membrane and a preparation method thereof, wherein PVA-co-PE nanofibers are used as a substrate, carboxylated carbon nanotubes (HOOC-MWCNT), copper nanowires (CuNWs) and nickel ferrite (NiFe 2 O 4 ) as fillers, and the fillers are evenly loaded into the substrate through vacuum assisted filtration, cross-linking and hot pressing processes. The substrate and the three fillers overlap and adsorb to form a three-dimensional network porous structure, and a nanofiber composite membrane with excellent electromagnetic shielding and mechanical properties is prepared. The electromagnetic shielding efficiency of the composite membrane reaches 59dB, and the maximum tensile stress reaches 12MPa.

[0040] Please refer to Figure 1 In the first aspect, the embodiment of the present application provides an electromagnetic shielding nanofiber composite membrane, comprising a three-dimensional skeleton substrate, and a conductive medium and a magnetic medium uniformly dispersed in the three-dimensional skeleton substrate, wherein the conductive medium comprises carboxylated carbon nanotubes and copper nanowires, and the magnetic medium comprises nickel ferrite. Among them, the mass proportion of the three-dimensional skeleton substrate in the electromagnetic shielding nanofiber composite membrane is 94-99%, and the mass ratio of carboxylated carbon nanotubes, copper nanowires and nickel ferrite is (1-2.5):(1-1.5):1.

[0041] Furthermore, the electromagnetic shielding nanofiber composite membrane uses PVA-co-PE nanofiber as a three-dimensional skeleton substrate, and the carboxylated carbon nanotubes, copper nanowires and nickel ferrite are uniformly loaded into the PVA-co-PE nanofibers through vacuum-assisted filtration, cross-linking and hot pressing processes. The PVA-co-PE nanofibers, carboxylated carbon nanotubes and copper nanowires overlap each other to form a three-dimensional mesh, so that the electromagnetic shielding nanofiber composite membrane presents a three-dimensional mesh porous structure, and the nickel ferrite is attached to the copper nanowires and PVA-co-PE nanofibers, which increases the heterogeneous contact area, and can achieve the effect of reducing magnetic force and increasing the scattering of electromagnetic waves.

[0042] Furthermore, the thickness of the electromagnetic shielding nanofiber composite membrane is 20-30 μm, the electromagnetic shielding effectiveness reaches 59 dB, and the maximum tensile stress reaches 12 MPa.

[0043] In a second aspect, the present invention provides a method for preparing the aforementioned electromagnetic shielding nanofiber composite membrane, comprising the following steps:

[0044] S1, isopropyl alcohol, deionized water and PVA-co-PE nanofibers are uniformly mixed using a high-speed shearing machine to prepare a PVA-co-PE nanofiber suspension with a fiber content of 1 wt%.

[0045] S2, mixing the PVA-co-PE nanofiber suspension prepared in step S1 with carboxylated carbon nanotubes, copper nanowires and nickel ferrite, stirring for 0.5-1h, and vacuum-assisted filtering to obtain a nanofiber composite membrane.

[0046] S3, immersing the nanofiber composite membrane in a glutaraldehyde crosslinking agent with a concentration of 1.5wt%, crosslinking the membrane by ultraviolet radiation crosslinking for 3-3.5h, then naturally air-drying, hot pressing, and obtaining an electromagnetic shielding nanofiber composite membrane (PVA-co-PE / HOOC-MWCNTs / CuNWs / NiFe 2 O 4 ).

[0047] Furthermore, in step S2, PVA-co-PE nanofibers account for 94-99% of the mass of the nanofiber composite membrane, and the mass ratio of carboxylated carbon nanotubes to copper nanowires and nickel ferrite is (1-2.5):(1-1.5):1.

[0048] Further, in step S2, the preparation method of carboxylated carbon nanotubes is: adding multi-walled carbon nanotubes to concentrated nitric acid, ultrasonicating for 1-2 hours, then adding an appropriate amount of concentrated sulfuric acid, placing at 55-65°C overnight, adding 2 times the volume of deionized water to dilute, freeze-drying, and collecting to obtain carboxylated carbon nanotube powder. Wherein, 1-1.2g of multi-walled carbon nanotubes is added to every 50mL of concentrated nitric acid, and the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 1:3. The inner diameter of the carboxylated carbon nanotubes is 5-6nm, the outer diameter is 15-16nm, and the length is 10-11μm.

[0049] Furthermore, in step S2, the preparation method of the copper nanowires is: copper chloride, octadecylamine and anhydrous glucose are reacted in a hydration reactor at a mass ratio of 1:1:(1.8-2.0) at 120°C for 8-9h. The diameter of the copper nanowires is 100-105nm and the length is 10-11μm.

[0050] Furthermore, in step S2, the preparation method of nickel ferrite is: react nickel nitrate nonahydrate and iron nitrate hexahydrate at a mass ratio of 1:(1-1.2) at 180° C. for 12-14 hours to obtain nickel ferrite with a spinel structure and a particle size of 30-35 nm.

[0051] Furthermore, in step S3, the solvent of the glutaraldehyde cross-linking agent is anhydrous ethanol.

[0052] Furthermore, in step S3, the hot pressing method is to sandwich the air-dried nanofiber composite membrane between two polyimide films, and then place them together in a hot press at 100-105° C. for 60-65 seconds.

[0053] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0054] 1. Preparation method

[0055] In the examples provided in this application, the inner diameter of the carboxylated carbon nanotubes is 5 nm, the outer diameter is 15 nm, and the length is 10 μm; the diameter of the copper nanowires is 100 nm, and the length is 10 μm; and the particle size of the nickel ferrite is 30 nm. The preparation methods of the three are as follows:

[0056] (1) Carboxylation of carbon nanotubes (HOOC-MWCNTs): 1 g of multi-walled carbon nanotubes (MWCNTs) was mixed with 50 mL of concentrated nitric acid and ultrasonicated for 1.5 h, and concentrated sulfuric acid (the volume ratio of concentrated sulfuric acid to concentrated nitric acid was 1:3) was added, and the mixture was placed at 60 °C overnight, diluted with 2 times the volume of deionized water, and freeze-dried;

[0057] (2) Copper nanowires (CuNWs): Copper chloride, octadecylamine and anhydrous glucose were reacted in a hydration reactor at a mass ratio of 1:1:1.8 at 120 °C for 8 h;

[0058] (3) Nickel ferrite (NiFe 2 O 4 ): Nickel nitrate nonahydrate and iron nitrate hexahydrate are reacted at 180°C for 12 hours in a mass ratio of 1:1.

[0059] Example 1

[0060] Example 1 provides a method for preparing an electromagnetic shielding nanofiber composite membrane, and the specific steps are as follows:

[0061] S1, using a high-speed shearing machine to disperse and mix isopropyl alcohol, deionized water and PVA-co-PE nanofibers to prepare a PVA-co-PE nanofiber suspension with a fiber content of 1 wt%.

[0062] S2, mixing the PVA-co-PE nanofiber suspension prepared in step S1 with HOOC-MWCNTs, CuNWs and NiFe 2 O 4 The components were mixed in a mass ratio of 10:0.05:0.05:0.05 and stirred for 0.5 h to obtain a multi-component suspension, which was then vacuum-assisted filtered at 0.1 MPa to obtain a nanofiber composite membrane.

[0063] S3, soaking the nanofiber composite membrane prepared in step S4 in a glutaraldehyde crosslinking agent (the solvent is anhydrous ethanol) with a concentration of 1.5wt%, placing the immersed nanofiber composite membrane under ultraviolet radiation for crosslinking for 3 hours, carefully taking it out with tweezers and air-drying it naturally, clamping the air-dried composite membrane with a polyimide film and placing it in a hot press at 105°C for 60 seconds to obtain an electromagnetic shielding nanofiber composite membrane.

[0064] Example 2 and Comparative Examples 1-2

[0065] The difference between Example 2 and Comparative Example 1-2 and Example 1 is that the mass ratio of the magnetic medium and the conductive medium is changed, as shown in the following table. The other contents are substantially the same as those in Example 1 and will not be repeated here.

[0066]

[0067]

[0068] Examples 3-5 and Comparative Examples 3-4

[0069] The difference between Examples 4-6 and Comparative Examples 1-3 and Example 1 is that the mass proportion of PVA-co-PE nanofibers is changed, as shown in the following table. The other contents are roughly the same as Example 1 and will not be repeated here.

[0070] project <![CDATA[Mass ratio (PVA-co-PE: HOOC-MWCNTs: CuNWs: NiFe 2 O 4 )]]> Example 1 10:0.25:0.15:0.10 Comparative Example 3 4:0.25:0.15:0.10 Example 3 8:0.25:0.15:0.10 Example 4 12:0.25:0.15:0.10 Example 5 15:0.25:0.15:0.10 Comparative Example 4 20:0.25:0.15:0.10

[0071] Comparative Example 5

[0072] The difference between Comparative Example 5 and Example 1 is that in step S2, the conductive medium CuNWs and the magnetic medium NiFe are not added. 2 O 4 The mass ratio of the substrate PVA-co-PE to the conductive medium HOOC-MWCNTs is 10:0.25. The other contents are substantially the same as those in Example 1 and will not be described herein.

[0073] Comparative Example 6

[0074] The difference between Comparative Example 6 and Example 1 is that in step S2, no magnetic medium NiFe is added. 2 O 4The mass ratio of the substrate PVA-co-PE to the conductive medium HOOC-MWCNTs and CuNWs is 10:0.25:0.15. The other contents are substantially the same as those in Example 1 and will not be described herein.

[0075] Comparative Example 7

[0076] The difference between Comparative Example 7 and Example 1 is that in step S2, the carboxyl carbon nanotube (HOOC-MWCNTs) powder is replaced with multi-walled carbon nanotubes (MWCNTs), that is, the PVA-co-PE nanofiber suspension is mixed with MWCNTs, CuNWs and NiFe 2 O 4 A nanofiber composite membrane was prepared by mixing in a mass ratio of 10:0.25:0.15:0.10. Other contents were substantially the same as those in Example 1 and will not be described herein.

[0077] Comparative Example 8

[0078] The difference between Comparative Example 8 and Example 1 is that in step S3, no glutaraldehyde crosslinking agent is added, and the nanofiber composite membrane prepared in step S2 is directly placed under ultraviolet radiation for 30 minutes to obtain a nanofiber composite membrane. The other contents are roughly the same as Example 1 and will not be repeated here.

[0079] Comparative Example 9

[0080] The difference between Comparative Example 9 and Example 1 is that the structure of the electromagnetic shielding nanofiber composite membrane is changed. Specifically, in step S2, PVA-co-PE nanofibers, HOOC-MWCNTs and CuNWs are first mixed to prepare a suspension A, and then NiFe 2 O 4 Prepare suspension B, and perform vacuum assisted filtration at 0.1 MPa in the order of suspension A-suspension B-suspension A, so that the prepared nanofiber composite membrane has a sandwich layer structure. Among them, PVA-co-PE / HOOC-MWCNTs / CuNWs is the outer layer, NiFe 2 O 4 The other contents are substantially the same as those in Example 1 and will not be described in detail here.

[0081] Comparative Example 10

[0082] The difference between Comparative Example 10 and Example 1 is that in step S3, the hot pressing step is deleted, that is, the nanofiber membrane obtained in step S2 is immersed in glutaraldehyde cross-linking agent, cross-linked by ultraviolet radiation, and then clamped out with tweezers and naturally air-dried to directly obtain an electromagnetic shielding nanofiber composite membrane. The other contents are roughly the same as Example 1 and will not be repeated here.

[0083] 2. Test Method

[0084] 1. Observe surface morphology and microstructure

[0085] The surface morphology and microstructure of the samples were observed using a thermal field scanning electron microscope (SU5000). Specifically, the samples were cut into small pieces of 0.5 cm*0.5 cm, adhered to the electron microscope stage with conductive glue, vacuum-sprayed with gold for 120 seconds, and then placed in an electron microscope for testing.

[0086] 2. Electromagnetic shielding performance test

[0087] (1) Resistivity and conductivity test

[0088] The resistivity and conductivity of the samples at different locations were tested using a dual-electrical four-probe tester model RTS-9, and the average value was calculated to obtain the final result.

[0089] (2) Electromagnetic shielding effectiveness (EMI SE) test

[0090] The electromagnetic shielding effectiveness of the samples was tested using a ZNB-20 vector network analyzer with a test bandwidth of 8.12-12.5 GHz.

[0091] 3. Mechanical properties test

[0092] The mechanical properties of the samples were tested using an INSTRON electronic universal testing machine model 68TM-10. The samples were cut into a size of 2 cm*0.5 cm, the tensile speed was set to 50 mm / s, and the test ended when the sample broke.

[0093] III. Analysis of test results of various embodiments and comparative examples

[0094] The surface morphology and microstructure of the electromagnetic shielding nanofiber composite membrane prepared in Example 1 were tested using Test Method 1 and compared with PVA-co-PE nanofibers.

[0095] See also Figures 2 to 4 As shown, Figure 2 The surface microstructure of PVA-co-PE nanofibers when magnified 1000 times. Figure 3 The surface microstructure of the electromagnetic shielding nanofiber composite membrane prepared in Example 1 is magnified 10,000 times. Figure 4 The surface microstructure of the electromagnetic shielding nanofiber composite membrane prepared in Example 1 is magnified 1000 times. It can be seen that the PVA-co-PE nanofiber provides a three-dimensional mesh substrate for the electromagnetic shielding nanofiber composite membrane. 2 O 4and CuNWs are evenly distributed inside the nanofibers, where PVA-co-PE, HOOC-MWCNTs and CuNWs overlap each other to form a special three-dimensional network structure, which makes the composite membrane have a good porous structure, and NiFe 2 O 4 It is tightly adhered to the three-dimensional network structure and forms a large-area heterostructure with the rod-shaped CuNWs and HOOC-MWCNTs. When electromagnetic waves are incident on the surface of the composite film, they will be repeatedly scattered and absorbed on the heterostructure surface, achieving the attenuation of electromagnetic waves.

[0096] The electromagnetic shielding performance and mechanical properties of the composite films prepared in Examples 1-5 and Comparative Examples 1-4 were tested using Test Methods 2 and 3, and the results are shown in the table below.

[0097]

[0098]

[0099] Refer to the table above, we can see that the fillers (HOOC-MWCNTs, CuNWs and NiFe 2 O 4 ) is 0.25:0.15:0.10 to achieve the best electromagnetic shielding effect of 59dB and mechanical properties of 12MPA. This is because the modified carbon nanotubes contain a large number of carboxyl groups, which can form hydrogen bonds with PVA-co-PE and improve the mechanical properties of the composite film. At the same time, the tubular and linear structures of carbon materials and copper nanomaterials can effectively avoid agglomeration during the film preparation process, which is conducive to the uniform dispersion of the two in the substrate. At the same time, the carbon-copper composite has better electrical conductivity, which is comparable to NiFe with an inverse spinel structure. 2 O 4 Mixing can form a "magnetic-electric" synergistic effect and improve the electromagnetic shielding performance of the film. When the content of HOOC-MWCNTs and CuNWs is too small, most of the NiFe 2 O 4 They are adsorbed on PVA-co-PE and have no contact with HOOC-MWCNTs and CuNWs, making it difficult to form a heterogeneous structure, resulting in the reduction of the electromagnetic shielding performance of the composite film.

[0100] It can also be seen that the increase in the mass proportion of the substrate (PVA-co-PE) will cause the electromagnetic shielding performance and mechanical properties of the composite film to increase first and then decrease. This is because when the substrate content is too high, the nanofiber slurry is relatively thick, which is difficult to filter during the preparation process, and the film-forming effect is poor. In addition, the holes in the composite film are easily blocked by coarse fibers or thick slurry, resulting in fewer pores for electromagnetic waves to enter and a poor scattering effect. When the substrate content is too low and there are too many dielectric fillers, the substrate is not enough to provide a good three-dimensional structural support, making the overall structure of the composite film relatively loose, with poor mechanical properties, and easy to crack during use. At the same time, too much filler will also cause it to stack, agglomerate, and distribute unevenly in the substrate, resulting in poor shielding effect.

[0101] The electromagnetic shielding performance and mechanical properties of the nanofiber composite membranes prepared in Comparative Examples 5-10 were tested using the methods in Test Methods 2 and 3, and the results are shown in the table below.

[0102]

[0103]

[0104] See also Figure 5 As shown in the table above, combined with the data of Example 1 and Comparative Examples 5-6, it can be seen that the filler lacks NiFe 2 O 4 The presence of CuNWs or the lack of CuNWs will reduce the electromagnetic shielding performance of the composite film, further illustrating the synergistic effect between the three fillers.

[0105] See also Figure 6 As shown, combined with the data of Example 1 and Comparative Examples 7-8 in the above table, it can be seen that the use of unmodified carbon nanotubes (MWCNTs) or the absence of a cross-linking agent will lead to a decrease in the mechanical properties of the composite film. This is because the modified carbon nanotubes (HOOC-MWCNTs) have a large number of carboxyl functional groups, which need to form hydrogen bonds with the PVA-co-PE molecular chains through a cross-linking reaction to improve the mechanical properties of the composite film.

[0106] Please refer to the table above. By comparing the data of Comparative Example 9 with that of Example 1, it can be seen that the electromagnetic shielding performance and mechanical properties of the nanofiber composite membrane prepared in Comparative Example 9 are relatively poor. This is because NiFe 2 O 4 As an intermediate layer alone, the degree of compounding with the upper and lower layers is not tight enough, and it cannot be in uniform contact with the other three raw materials to form a large number of heterogeneous interfaces, which shows that the improvement of the composite membrane structure in this application has significantly improved the electromagnetic shielding performance and mechanical properties of the membrane.

[0107] Continuing to refer to the above table, by comparing the data of Comparative Example 10 with Example 1, it can be seen that the electromagnetic shielding performance and mechanical properties of the nanofiber composite membrane prepared in Comparative Example 10 are slightly lower. This is because hot pressing can squeeze out excess solvent in the composite membrane, accelerate the formation of hydrogen bonds between the raw materials, and also make its internal structure tighter, which is beneficial to improving the electromagnetic shielding performance and mechanical properties.

[0108] In summary, this application uses PVA-co-PE as the substrate, HOOC-MWCNT, CuNWs and NiFe 2 O 4 As fillers, the fillers are evenly loaded into the substrate through vacuum-assisted filtration, cross-linking and hot pressing processes. The substrate and the three fillers overlap and adsorb to form a three-dimensional mesh porous structure, and a nanofiber composite membrane with excellent electromagnetic shielding and mechanical properties is prepared. Among them, the porous structure promotes the scattering and absorption of electromagnetic waves by the composite membrane. The large number of heterogeneous contact surfaces formed by the uniform dispersion of the three fillers in the substrate increases the dipole polarization effect, optimizes the impedance matching, and makes the composite membrane show better electromagnetic attenuation and shielding performance. In addition, a large number of hydrogen bonds can be formed between the HOOC-MWCNT and PVA-co-PE obtained by modifying carbon nanotubes through cross-linking, which improves the mechanical properties of the composite membrane.

[0109] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. An electromagnetic shielding nanofiber composite membrane, characterized in that: It comprises a three-dimensional skeleton substrate, and a conductive medium and a magnetic medium uniformly dispersed in the three-dimensional skeleton substrate; the electromagnetic shielding nanofiber composite membrane has a three-dimensional mesh porous structure; the electromagnetic shielding nanofiber composite membrane has a thickness of 20-30 μm, an electromagnetic shielding effectiveness of 59 dB, and a maximum tensile stress of 12 MPa; The mass proportion of the three-dimensional skeleton substrate in the electromagnetic shielding nanofiber composite membrane is 94-99%.

2. The electromagnetic shielding nanofiber composite membrane according to claim 1, characterized in that: The conductive medium includes carboxylated carbon nanotubes and copper nanowires, and the magnetic medium includes nickel ferrite.

3. The electromagnetic shielding nanofiber composite membrane according to claim 2, characterized in that: The mass ratio of the carboxylated carbon nanotubes, the copper nanowires and the nickel ferrite is (1-2.5):(1-1.5):

1.

4. The electromagnetic shielding nanofiber composite membrane according to claim 1, characterized in that: The electromagnetic shielding nanofiber composite membrane uses PVA-co-PE nanofibers as a three-dimensional skeleton substrate, and the carboxylated carbon nanotubes, the copper nanowires and the nickel ferrite are uniformly loaded into the PVA-co-PE nanofibers through vacuum-assisted filtration, cross-linking and hot pressing processes.

5. The electromagnetic shielding nanofiber composite membrane according to claim 4, characterized in that: The PVA-co-PE nanofibers, the carboxylated carbon nanotubes and the copper nanowires are overlapped with each other to form a three-dimensional mesh porous structure.

6. A method for preparing the electromagnetic shielding nanofiber composite membrane according to any one of claims 1 to 5, characterized in that: The steps include: S1, isopropyl alcohol, deionized water and PVA-co-PE nanofibers are uniformly mixed using a high-speed shearing machine to prepare a PVA-co-PE nanofiber suspension with a fiber content of 1 wt%; S2, mixing the PVA-co-PE nanofiber suspension prepared in step S1 with carboxylated carbon nanotubes, copper nanowires and nickel ferrite, stirring for 0.5-1h, and vacuum-assisted filtration to obtain a nanofiber composite membrane; the PVA-co-PE nanofibers account for 94-99% of the mass of the nanofiber composite membrane; the mass ratio of the carboxylated carbon nanotubes to the copper nanowires and the nickel ferrite is (1-2.5):(1-1.5):1; S3, immersing the nanofiber composite membrane in a glutaraldehyde crosslinking agent with a concentration of 1.5 wt%, crosslinking is performed by ultraviolet radiation crosslinking method, and then naturally air-drying and hot pressing to obtain the electromagnetic shielding nanofiber composite membrane.

7. The method for preparing the electromagnetic shielding nanofiber composite membrane according to claim 6, characterized in that: In step S2, the preparation method of the carboxylated carbon nanotubes is to mix the multi-walled carbon nanotubes with concentrated nitric acid and ultrasonicate for 1-2 hours, add concentrated sulfuric acid, place at 55-65° C. overnight, then add 2 times the volume of deionized water to dilute, freeze-dry, and obtain carboxylated carbon nanotube powder.

8. The method for preparing the electromagnetic shielding nanofiber composite membrane according to claim 7, characterized in that: In the method for preparing carboxylated carbon nanotubes, the volume ratio of the concentrated sulfuric acid to the concentrated nitric acid is 1:

3.

9. The method for preparing the electromagnetic shielding nanofiber composite membrane according to claim 6, characterized in that: In step S3, the hot pressing method is to sandwich the air-dried nanofiber composite membrane between two polyimide films and place them together in a hot press at 100-105° C. for 60-65 seconds.

10. The method for preparing the electromagnetic shielding nanofiber composite membrane according to claim 9, characterized in that: In step S3, the time of ultraviolet light irradiation cross-linking is 3-3.5 hours.

Citation Information

Patent Citations

  • Flexible ultrathin high-heat-conductivity electromagnetic shielding thin membrane and preparation method thereof

    CN110241613A

  • Flexible MXene protein composite membrane with electromagnetic shielding and pressure-sensitive characteristics as well as preparation method and application of flexible MXene protein composite membrane

    CN114702709A

  • Electromagnetic shielding composite paper and preparation method thereof

    CN116752380A

  • Electromagnetic shielding nanofiber composite membrane as well as preparation method and application thereof

    CN118591168A

  • Electromagnetic wave shielding material and method for manufacturing the same

    JP2005191384A